2022
DOI: 10.3390/su14074232
|View full text |Cite
|
Sign up to set email alerts
|

Responses in Soil Carbon and Nitrogen Fractionation after Prescribed Burning in the Montseny Biosphere Reserve (NE Iberian Peninsula)

Abstract: Prescribed fire is one of the most widely-used management tools to recover encroached rangelands. Fire has been reported to cause changes in the soil physical and chemical properties. However, the legacy effects of former plant species on soil responses to fire remains unknown. The legacy effect of the former extant plant species on soil carbon (C) and nitrogen (N) fractionation distribution after prescribed burning in topsoil (0–5 cm and 5–10 cm) was investigated in Mediterranean shrublands in Montseny. We sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For example, Bielefeld et al [85] determined that, in general, at this depth, fire directly affects soil physicochemical properties as they are exposed to surface heating [12]. This has been corroborated by works such as Chowdhury et al [73] who found that a large part of the thermal energy generated during a fire is lost in the atmosphere, and a smaller amount is radiated downward and absorbed by organic matter. In this context, regarding the bulk density of the most recent and high severity fire (1B-HS: 2019, 2 years since the fire) (Table 2), it coincides with the results obtained by Goforth et al [84] and Chandra and Bhardwaj [18] who showed that when fires are of high severity, the bulk density tends to increase in value and generates greater soil compaction.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, Bielefeld et al [85] determined that, in general, at this depth, fire directly affects soil physicochemical properties as they are exposed to surface heating [12]. This has been corroborated by works such as Chowdhury et al [73] who found that a large part of the thermal energy generated during a fire is lost in the atmosphere, and a smaller amount is radiated downward and absorbed by organic matter. In this context, regarding the bulk density of the most recent and high severity fire (1B-HS: 2019, 2 years since the fire) (Table 2), it coincides with the results obtained by Goforth et al [84] and Chandra and Bhardwaj [18] who showed that when fires are of high severity, the bulk density tends to increase in value and generates greater soil compaction.…”
Section: Discussionmentioning
confidence: 90%
“…Soil samples were taken at each corner of each plot at a depth of 0-10 cm, using standardized metal cores (6 cm diameter, 10 cm height, 283 cm 3 volume) [71]. The 0-10 cm depth was considered because generally, at this depth, fire increases soil temperature and affects the main physical and chemical properties, as reported in previous research [72,73]. In each plot, 4 samples were taken separately for further analysis of bulk density, texture, pH, soil organic matter (SOM), and total soil nutrients (3 years × 2 study sites × 2 treatments × 3 plots × 4 samples = 144 individual samples).…”
Section: Soil Sampling and Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Soil nitrogen concentration (N) (%) was assessed using the Micro-Kjeldahl method [48], and soil organic matter (OM) (%) was determined using the Walkley and Black method [49]. Potassium (K) (ppm) was estimated using the NH4 method [50], while soil available phosphorus (P) (ppm) was determined using the modified Olsen method [51]. Additionally, electrical conductivity (mmhos/cm) (EC) was evaluated using a conductivity meter.…”
Section: Soil Physico-chemical Properties Analysesmentioning
confidence: 99%
“…Soil organic carbon (SOC) and soil organic matter (SOM) were determined by the method of Walkley and Black [65,66], for which the sample was placed in an oven at 125 • C for 45 min, after oxidation in a solution of K 2 Cr 2 O 7 /H 2 SO 4 . Soil ammonia nitrogen concentration (SAN; mg/kg) was measured by the colorimetric method [67], while soil available phosphorus (P; mg/kg), potassium (K; meq/100 g), calcium (Ca; meq/100 g), and magnesium (Mg; meq/100 g) were determined by the modified Olsen method [68].…”
Section: Soil Physico-chemical Properties Analysesmentioning
confidence: 99%